Review of EGFR TKIs in Metastatic NSCLC, Including Ongoing Trials - Melosky, Barbara (Frontiers in Oncology, 2014)
Recent clinical trials have demonstrated the efficacy of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) in the treatment of patients with advanced metastatic non-small cell lung cancer. Most of these recent trials were conducted in patients with EGFR mutation-positive tumours. As our knowledge of the EGFR mutation and its resistant pathways develops, the complexity of the situation expands. This article briefly reviews the pivotal trials leading to approval of EGFR TKIs in the first-line setting for patients with EGFR mutation-positive non-small cell lung carcinomas. It discusses the historical use of EGFR TKIs after the first line setting in unselected patients and briefly describes ongoing trials.